Stability of Smyd1 in endothelial cells is controlled by PML-dependent SUMOylation upon cytokine stimulation. Issue 1 (15th January 2021) - Becker, Samuel; Steinemann, Gustav; Karle, Weronika; Roos, Kerrin; Liem, Celine Huajia; Muralikumar, Shalini; Volkamer, Andrea; Munz, Barbara; Zakrzewicz, Andreas; Berkholz, Janine
Abstract : Smyd1 is an epigenetic modulator of gene expression that has been well-characterized in muscle cells. It was recently reported that Smyd1 levels are modulated by inflammatory processes. Since inflammation affects the vascular endothelium, this study aimed to characterize Smyd1 expression in endothelial cells. We detected Smyd1 in human endothelial cells (HUVEC and EA.hy926 cells), where the protein was largely localized in PML nuclear bodies (PML-NBs). By transfection of EA.hy926 cells with expression vectors encoding Smyd1, PML, SUMO1, active or mutant forms of the SUMO protease SuPr1 and/or the SUMO-conjugation enzyme UBC9, as well as Smyd1- or PML-specific siRNAs, in the presence or absence of the translation blocker cycloheximide or the proteasome-inhibitor MG132, and supported by computational modeling, we show that Smyd1 is SUMOylated in a PML-dependent manner and thereby addressed for degradation in proteasomes. Furthermore, transfection with Smyd1-encoding vectors led to PML up-regulation at the mRNA level, while PML transfection lowered Smyd1 protein stability. Incubation of EA.hy926 cells with the pro-inflammatory cytokine TNF-α resulted in a constant increase in Smyd1 mRNA and protein over 24 h, while incubation with IFN-γ induced a transient increase in Smyd1 expression, which peaked at 6 h and decreased to control values within 24 h. The IFN-γ-induced increase in Smyd1 was accompanied by more Smyd1 SUMOylation and more/larger PML-NBs. In conclusion, our data indicate that in endothelial cells, Smyd1 levels are regulated through a negative feedback mechanism based on SUMOylation and PML availability. This molecular control loop is stimulated by various cytokines.